Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 decade ago

Factor the following polynomial:?

3x^3 - 9x^2

A) x(3x^2 - 9)

B) 3x^2(x - 3)

C) (x + 3)(x - 9)

D) 2x(3 - x)(6 - x)

2.)Factor the following polynomial:

3y - 6x + 4xy - 2y^2

A) 2xy(x^2 - 3y + 2)

B) (x + 3y)(3x - y)

C) (2x - y)(2y - 3)

D) 3x(3 - x)(2 + y)

3.)Factor the following polynomial:

12a^2 - 4ac + 3ab - bc

A) (3b - a)(a + 4c)

B) 3a(2a - b + 3c)

C) 2(3a - b)(4a + bc)

D) (4a + b)(3a - c)

4.)Factor the following polynomial:

35g^2h - 15gh^2

A) 5gh(7g - 3h)

B) 7g^2(5h - 8g)

C) 5(7 - g)(8- h)

D) 15gh(g - 7)

5.)Factor the following polynomial:

6uv - 3v^3 + 4u - 2v^2

A) (2u - v^2)(3v + 2)

B) (3u - 2v)(2u - 3)

C) 3uv(2u - 3v + 2)

D) 2v^2(3u - v)(2 - v^2)

6 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    1.b

    2.c

    3.d

    4.a

    5.a

  • 1 decade ago

    1)

    3x^3 - 9x^2

    = 3(x^3 - 3x^2)

    = 3x^2(x - 3)

    (answer B)

    2)

    3y - 6x + 4xy - 2y^2

    = 4xy - 2y^2 - 6x + 3y

    = (4xy - 2y^2) - (6x - 3y)

    = 2y(2x - y) - 3(2x - y)

    = (2x - y)(2y - 3)

    (answer C)

    3)

    12a^2 - 4ac + 3ab - bc

    = (12a^2 - 4ac) + (3ab - bc)

    = 4a(3a - c) + b(3a - c)

    = (3a - c)(4a + b)

    (answer D)

    4)

    35g^2h - 15gh^2

    = 5(7g^2h - 3gh^2)

    = 5gh(7g - 3h)

    (answer A)

    5)

    6uv - 3v^3 + 4u - 2v^2

    = -3v^3 - 2v^2 + 6uv + 4u

    = (-3v^3 - 2v^2) + (6uv + 4u)

    = -v^2(3v + 2) + 2u(3v + 2)

    = (3v + 2)(-v^2 + 2u)

    (answer A)

  • 1 decade ago

    a) 3x^3 - 9x^2 = 3x^2(x-3)

    b)3y - 6x + 4xy - 2y^2= 3(y-2x) +2y (2x-y) = (y-2x)(3-2y) = (2x-y)(2y-3)

    c) 12a^2 - 4ac + 3ab - bc = 4a(3a -c) + b (3a-c) = (4a+b)(3a-c)

    d)35g^2h - 15gh^2 = 5gh(7g-3h)

    e) 6uv - 3v^3 + 4u - 2v^2 = 3v(2u - v^2) + 2 (2u - v^2) = (3v+2)(2u-v^2)

  • 1 decade ago

    3x^3 - 9x^2 = 3x^2(x - 3)

  • How do you think about the answers? You can sign in to vote the answer.
  • 1 decade ago

    3x^3 - 9x^2 = 3x^2(x - 3) (B)

  • 5 years ago

    4x^2-25 (2x+5)(2x-5) check: 4x^2-10x+10x-25 4x^2-25

Still have questions? Get your answers by asking now.